Ayo Sinau Basa Jawa: Bahan Digital Penunjang Pembelajaran Kosakata Bahasa Jawa Berbasis Multimedia - Ella Rizky Endryanti; Roekhan Roekhan; Primardiana Hermilia Wijayati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This research aims to develop digital interactive teaching materials entitled "Ayo Sinau Basa Jawa" (Let's Learn Javanese) for students in grade I in elementary school. The research and development method used is ADDIE. The measures taken in this development research are analysis, design, development, implementation, dan Evaluation. The digital teaching method named Ayo Sinau Basa Jawa is a multimedia based interactive teaching material which provides menu called sinau (learn) and gladhen (practice) inside. The "sinau" material is presented by integrating pictures, sounds, and videos while "gladhen" is given in a form of quizzes. Products developed were validated by three experts according to the aspects assessed, namely aspects of content, language and multimedia. The content validation results obtained a score of 96%, the results of language validation obtained a score of 93%, and the results of multimedia validation scored 93%. The result of this study is that the product is valid, so it is capable of being utilized and is attractive and effective to be used by elementary school students.Abstrak: Penelitian ini bertujuan mengembangkan bahan ajar interaktif berupa bahan digital Ayo Sinau Basa Jawa bagi siswa kelas I Sekolah Dasar. Metode penelitian dan pengembangan yang digunakan adalah model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Bahan digital Ayo Sinau Basa Jawa merupakan bahan ajar interaktif berbasis mulimedia yang menyediakan menu sinau (belajar) dan gladhen (latihan) didalamnya. Materi sinau disajikan dengan mengintegrasikan media gambar, audio dan video, sedangkan gladhen disajikan dalam bentuk kuis. Produk yang dikembangkan divalidasi oleh tiga ahli sesuai aspek yang dinilai, yakni aspek isi, bahasa, dan multimedia. Hasil validasi isi memperoleh skor 96%, hasil validasi bahasa memperoleh skor 93%, dan hasil validasi multimedia memperoleh skor 93%. Hasil penelitian ini menunjukkan bahwa produk telah valid sehingga layak dan efektif digunakan oleh siswa Sekolah Dasar.